Self compassion dan resiliensi pada perawat pasien Covid-19 - Tri Ananda Rahayu; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2022)
Abstract The study was conducted to determine the relationship between self-compassion and the resilience of nurses for Covid-19 patients. The research design used is a quantitative approach, namely correlational research. Participants in this study involved nurses for Covid-19 patients who worked in several hospitals that served positive Covid-19 patients in Surabaya Raya, with a total of 82 nurses. Data acquisition in this study was carried out by distributing a questionnaire link consisting of a resilience scale and a self-compassion scale to research participants. The research data then analyzed using parametric statistics, namely Product Moment correlation in the SPSS version 25.00 program, the results obtained a correlation score of 0.717 with a value of sig = 0.000 (p <0.05). This indicates that there is a significant positive relationship between resilience and self-compassion. This positive and significant relationship indicates the higher self-compassion in nurses with Covid-19 patients, the higher resilience in nurses with Covid-19 patients. Likewise, if self-compassion in nurses for Covid-19 patients is low, resilience in nurses will also be low. Keywords: Resilience, Self Compassion